Fungsi Hasil Laboratorium Forensik Sebagai Bukti dalam Tindak Pidana Narkotika - Achmad Miftah Farid; Novi Nur Indahsari (Jurnal USM Law Review)
This research aims to examine the position of forensic laboratory analysis results within the legal system based on Law Number 35 of 2009 concerning Narcotics, and the function of forensic laboratory results as evidence in narcotics criminal cases at the Sukoharjo Police Resort. The forensic laboratory plays an important role in proving narcotics cases, including in the Sukoharjo Police Resort area, by ensuring the identification of the type and concentration of narcotics as valid evidence in court. Unlike previous studies, the focus of this research is on the validity of forensic evidence in supporting justice in narcotics cases, particularly in the Sukoharjo area. The research method used is normative juridical with an analytical approach to relevant legislation, as well as using primary data from Law Number 35 of 2009, the Criminal Procedure Code, and the Police Medical Regulations. Research findings indicate that forensic laboratories play a central role in proving drug-related crimes by providing valid scientific analysis, which also influences judges' considerations in the criminal justice system. Law Number 35 of 2009 has provided a clear legal basis, but the validity of forensic laboratory results can be questioned if there is damage or contamination of the evidence. This study highlights the importance of more optimal forensic evidence management at Sukoharjo Police Station and recommends the enhancement of quality control procedures to minimize these obstacles in order to ensure justice and legal certainty.